Theoretical Study on (n,n)-Nanotubes Rolled-up from B/N Substituted Me-Graphene - Hong-Chao Luo; Feng-Yin Li; Ya-Nan Zhang; Hong-Xing Zhang; Roberts I. Eglitis; Ran Jia (Crystals, 2023)
In this work, the <semantics><mfenced>n,n</mfenced></semantics>-type nanotube systems rolled up from the B/N substituted Me-graphene (i.e., Me-CBNT and Me-CNN, respectively) were investigated with the aid of the density functional theory (DFT). Due to the lattice dynamic instabilities until <semantics>n=10</semantics>, the <semantics><mfenced>n,0</mfenced></semantics> and <semantics><mfenced>n,m</mfenced></semantics> nanotube systems were not involved in this study. According to our calculations at the Perdew-Burke-Ernzerhof (PBE) level, the <semantics><mfenced>n,n</mfenced></semantics> Me-CBNT and Me-CNNT systems possess excellent mechanical strengths. The Young’s moduli of Me-CBNTs can reach 60% of single-walled carbon nanotubes (SWCNTs), while their mass densities are only around 70% of SWCNTs. Based on the fully relaxed geometric configurations at the PBE level, the electronic configurations of the related nanotubes were evaluated by using the global hybrid functional B3LYP with 36% Fock exchanges. The <semantics><mfenced>n,n</mfenced></semantics> Me-CBNTs are metallic, while the <semantics><mfenced>n,n</mfenced></semantics> Me-CNNTs are semiconductors with the inherent band gaps in the range of 3.08 eV to 3.31 eV. The Bloch flat bands appear on both sides of their Fermi levels, indicating the localized charge carriers. Their band edge arrangements imply that these materials are promising candidates for the photocatalytic water splitting reactions at certain pH values.